2010
DOI: 10.1002/14651858.cd007511.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic versus open surgery in small bowel obstruction

Abstract: Although data from retrospective clinical controlled trials suggest that laparoscopy seems feasible and better in terms of hospital stay and mortality reduction, high quality randomised controlled trials assessing all clinically relevant outcomes including overall mortality, morbidity, hospital stay and conversion are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
52
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(54 citation statements)
references
References 13 publications
1
52
0
1
Order By: Relevance
“…Duron et al [241] suggested that the rate of primary or secondary recurrence (12 and 18 %, respectively) was not different after open compared to laparoscopic surgery (LE 2b). Neither RCTs nor prospective controlled studies on the laparoscopic approach to SBOs are available in the literature [242].…”
Section: Small Bowel Obstruction Due To Adhesionsmentioning
confidence: 99%
“…Duron et al [241] suggested that the rate of primary or secondary recurrence (12 and 18 %, respectively) was not different after open compared to laparoscopic surgery (LE 2b). Neither RCTs nor prospective controlled studies on the laparoscopic approach to SBOs are available in the literature [242].…”
Section: Small Bowel Obstruction Due To Adhesionsmentioning
confidence: 99%
“…7,8 Strangulated obstructions are surgical emergencies, and if not treated quickly lead to bowel ischemia and further morbidity and mortality. 8-10 Surgery for complete obstructions without known strangulation is controversial, but if medical therapy fails surgery is absolutely necessary. 7 Though management principles have not changed dramatically over the past decade, the population of patients continues to evolve, and thus the disease process must be reviewed to understand whether elderly patients have similar presentations, management, and outcomes as younger adults.…”
Section: Introductionmentioning
confidence: 99%
“…Sin embargo, existe información limitada sobre la seguridad de la laparoscopía en OIB y sus resultados en términos de exactitud diagnóstica y tasas de conversión varían considerablemente entre las distintas series publicadas [7][8][9] .…”
Section: Introductionunclassified